Hereditary haemorrhagic telangiectasia: a questionnaire based study to delineate the different phenotypes caused by endoglin and ALK1 mutations. Issue 8 (14th August 2003) - Berg, J; Porteous, M; Reinhardt, D; Gallione, C; Holloway, S; Umasunthar, T; Lux, A; McKinnon, W; Marchuk, D; Guttmacher, A
Abstract : Background : Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant vascular dysplasia characterised by mucocutaneous telangiectasis, epistaxis, gastrointestinal haemorrhage, and arteriovenous malformations in the lung and brain. Causative mutations for HHT have been identified in two genes, endoglin and ALK1, which encode proteins involved in serine-threonine kinase signalling in the endothelial cell. Methods : A number of people affected with HHT had completed a postal questionnaire as part of an international study to delineate the HHT phenotype. We identified questionnaires completed by subjects in whom we had identified a mutation in endoglin or ALK1. Further questionnaires were sent to families with known mutations. Data were only included from questionnaires returned by people known to carry disease causing mutations. Results : Questionnaires were completed by 83 subjects with known mutations. Of these, 49 had endoglin mutations (HHT1) and 34 had ALK1 mutations (HHT2). Subjects with HHT1 reported an earlier onset of epistaxis (p=0.01) and telangiectasis (p=0.0001) than those with HHT2. Pulmonary arteriovenous malformations were only reported in the endoglin mutation group in our study (p<0.001). Conclusions : Our questionnaire based study provides evidence that the HHT phenotype caused by mutations in endoglin (HHT1) is distinct from, and more severe than, HHT caused by mutations in ALK1 (HHT2). This has significant implications for diagnosis, screening, and treatment in the two different forms of HHT, as well as for understanding the pathogenesis of the disease.